Preservation Under Siege: Adaptive Conservation Approaches for Yemen’s Heritage - Al-Kebsi, Lames (University of Waterloo, 2025)
Yemen is no stranger to conflict. In fact, Yemen’s urban heritage, marked by tower houses and fortifications, reflects enduring architecture and craftsmanship developed over centuries. Towards the end of the 20th century, international interest in the preservation of Islamic cities placed Yemen center stage, leading to the award of three UNESCO World Heritage titles within a decade and to major publications and conservation projects. However, this momentum stalled following the 2011 Arab Spring revolution and the devastating coalition-led aerial raids in 2015, which caused the loss of many historical sites and disrupted the passing down of traditional construction techniques from one generation to the next. The thesis explores heritage preservation amidst Yemen’s ongoing conflict. Unlike existing scholarship that anticipates a stable government and resumption of foreign aid, this thesis proposes adaptive and local solutions for preserving Yemen’s heritage in its current, war-torn reality. It explores three proposals: re-purposing abandoned settlements of Yemenite Jews as shelters for displaced refugees, leveraging the Yemeni diaspora as potential donors, and utilizing the highly debated waqf system as a self-sustaining mechanism. The village of Bayt Baws in Sana’a is introduced as a case study, providing a grounded, culturally resonant, and logistically feasible model for heritage preservation in Yemen today.
Keywords: architecture; heritage preservation; Jewish heritage; Yemen; Bayt Baws; waqf; diaspora; conflict; resilience; restoration; conservation